2015
DOI: 10.1007/s40328-015-0106-8
|View full text |Cite
|
Sign up to set email alerts
|

Seismotectonic content by the source parameters of the 10 June 2012 Ölüdeniz-Fethiye (Dodecanese Islands) Mw 6.1 earthquake and aftershocks (southwestern Turkey)

Abstract: A detailed source and rupture process analyzes of the 10 June 2012 Ö lüdeniz-Fethiye (Dodecanese Islands; Mw 6.1) earthquake has been carried out using inversion of both complex body waves and strong ground motion records. The rupture starting from the hypocenter propagated gradually to the southwest. The main rupture is modeled by a main asperity located 2-3 km beneath the hypocenter and two small asperities. The size of the effective source area is about 24 9 12 km, the rupture duration was approximately 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Based on the focal mechanisms and distribution of epicenters, Görgün et al () suggested the activation of a NW–SE‐trending left lateral strike‐slip fault with a reverse component. On the other hand, Dogan, Irmak, Karakas, and Kalafat () suggested that oblique faulting connected with NW–SE extension is more dominant than the strike‐slip component, which forms the area between Fethiye Bay and the Rhodes Basin.…”
Section: Study Areamentioning
confidence: 99%
“…Based on the focal mechanisms and distribution of epicenters, Görgün et al () suggested the activation of a NW–SE‐trending left lateral strike‐slip fault with a reverse component. On the other hand, Dogan, Irmak, Karakas, and Kalafat () suggested that oblique faulting connected with NW–SE extension is more dominant than the strike‐slip component, which forms the area between Fethiye Bay and the Rhodes Basin.…”
Section: Study Areamentioning
confidence: 99%
“…The most recent earthquake activity occurred off Fethiye Bay on June 10, 2012, which had a mainshock of Mw = 6 due to activation of NW–SE trending left‐lateral strike‐slip fault (Görgün et al, 2014). On the other hand, Doğan et al (2016) suggested that oblique faulting connected with NW–SE extension, which forms the area between Fethiye Bay and the Rhodes Basin, is dominant.…”
Section: Regional Settingsmentioning
confidence: 99%